If a + b + c = 0, then find the value of
[(b–c)/a + (c–a)/b + (a–b)/c].[a/(b–c) + b/(c–a) + c/(a–b)]
(In reply to
The Process by K Sengupta)
(To state that a, b and c are not equal still allows a condition such as a=1, b=1 and c=5 which will also result in an undefined solution), thus the following must be true in order to find a solution:
(a <> b) AND (a <> c) AND (b <> c) AND
(a <> 0) AND (b <> 0) AND (c <> 0)
By inspection and simple substitution where a+b+c=0
[(b–c)/a + (c–a)/b + (a–b)/c].[a/(b–c) + b/(c–a) + c/(a–b)] = 9

Posted by Dej Mar
on 20060514 16:02:41 